Haematological parameters do senesce in the wild: evidence from different populations of a long‐lived mammal. (22nd November 2014) - Jégo, M.; Lemaître, J.‐F.; Bourgoin, G.; Capron, G.; Warnant, C.; Klein, F.; Gilot‐Fromont, E.; Gaillard, J‐M.
Abstract Increasing evidence of senescence has been reported from long‐term studies of wild populations. However, most studies have focused on life‐history traits like survival, reproduction or body mass, generally from a single intensively monitored population. However, variation in the intensity of senescence across populations, and to a lesser extent between sexes, is still poorly understood. In addition, the pattern of age‐specific changes in haematological parameters remains virtually unknown to date for any population of vertebrate living in the wild. Using repeated blood samples collected from known‐aged (2–15 years of age) roe deer (Capreolus capreolus) from two populations facing highly different environmental conditions, we filled the gap. In particular, we investigated age‐specific changes in haematocrit, albumin and creatinine. We reported clear evidence of senescence in all haematological parameters. Moreover, senescence patterns differed between sexes and populations. The rate of senescence was higher in males than in females for haematocrit with no site difference. On the other hand, the rate of senescence in creatinine was higher at Trois Fontaines than at Chizé with no sex difference. Our findings provide a first demonstration of age‐specific declines in haematological parameters in wild populations of large herbivores and show that the process of senescence in vertebrates is not restricted to body mass or fitness components. We also demonstrate that the senescence pattern of haematological parameters is context dependent and varies both between sexes and according to environmental conditions.